Generation of silver nanoparticles in a plasma-liquid system with a secondary discharge supported by a rotating gliding discharge - Chernyak, V.Ya.; Iukhymenko, V.V.; Iukhymenko, K.V.; Kolomiiets, O.V.; Samchenko, Y.M.; Hamazin, D.K.; Goriachko, A.M. (Вопросы атомной науки и техники, 2019)
Generation of silver nanoparticles in plasma-liquid system with secondary discharge that supported by rotating gliding discharge was investigated in work. Parameters of liquids after plasma treatment were investigated by absorption spectroscopy method. The Atomic Force Microscope (AFM) was used to determine the particle sizes obtained during the processing.